Socrates in Russia - DeBlasio, Alyssa; Juharyan, Victoria (Contemporary Russian Philosophy, 2022)
This volume explores the influence of the Socratic legacy on philosophy and literature in the Russian, East European, and Soviet contexts, including the work of Skovoroda, Radishchev, Herzen, Dostoevsky, Rozanov, Bely, Narbut, Bulgakov, and many others.